SENIOR HIGH SCHOOL ACADEMIC PROGRESSION IN MATHEMATICS - Mirabueno, Julie Ann S; Boyon, Ma Carolina L (PEOPLE: International Journal of Social Sciences, 2020)
One of the strategies in accelerating the country’s human capital development is to achieve quality accessible, relevant, and liberating basic education for all. This can be done through various programs in the department which develop and improve and continue curricular reforms. Hence, developing an intervention suited to 21st century learners’ needs specifically for the new basic education curriculum can be challenge. The study describes the trends of Senior High School Academic Progression in Mathematics of a school district in a Province of the Philippines through quantitative analysis that tracks students’ performance in Grade 9, Grade 10 and Grade 11 mathematics using National Career Assessment Examination (NCAE) Mathematical Ability results, National Achievement Test (NAT) Mathematics results, General Mathematics and Statistics and Probability ratings. Logical Reasoning Test (LRT) results was used as an additional explanatory variable for a Grade 11 Mathematics performance regression equation. Research results revealed that there are pairwise significant relationships between Grade 11 General Mathematics and Statistics and Probability academic performance with a) NCAE Mathematical Ability, b) NAT Grade 10 Mathematics and c) Logical Reasoning. Recommended interventions, for improving Senior and Junior High Mathematics suited to learner’s needs were designed.